Variations of Two Pools of Glycogen and Ethanol inSaccharomyces carlsbergenesis - P. Jadhav, J.; S. Dake, M.; B. Patil, N. (Asian Journal of Chemistry, 2010)
Saccharomyces carlsbergenesis maintains two pools of glycogen, one soluble and the other insoluble and also topographically separated and metabolize them separately. Glycogen gets accumulated in the cells and its concentration greatly varies. The variations of these two pools of glycogen as a function of fermentation time, different sugar concentrations, different peptone concentrations and in different media when studied shows that sucrose is a better sugar than glucose. Since the yield of ethanol and glycogen is higher, optimum insoluble glycogen and ethanol are found to be at 36 h of fermentation. Though glycogen may serve as a substrate under anaerobic conditions for ethanol production, the availability of co-enzymes, co-factors and the necessary enzymes for the conversion are equally important.